Scout and the sausage thief - Lewis, Gill (Puppy Academy, 2016)
"Meet the students at Puppy Academy a team of plucky puppies learning to be working dogs. Scout wants nothing more than to be a police dog, just like her mom and dad. But when she fails her test, Scout isn't sure she'll ever earn her badge until, that is, a sausage thief strikes. It's up to Scout to catch the culprit and save the day"--